Sequential geriatric assessment in older patients with colorectal cancer during chemotherapy: subgroup analysis of a prospective, multicenter study EpiReal 75 - Li, Moying; Schulte, Nadine; Elting, Frederik; Winkler, Eva C.; Hetjens, Svetlana; Berger, Anne Katrin; Zschäbitz, Stefanie; Hofmann, Jan; Hofmann, Jasmin; Hilbertz, Lieselotte; Kuhn, Merlin; Khakzar, Carolin; et al. (Oncology research and treatment, 2022)
Colorectal cancer (CRC) is a disease of older patients, but evidence-based guidelines for chemotherapy in older patients are scarce. Geriatric assessment (GA) evaluates a patient’s functional status (FS) and helps in decision-making when choosing chemotherapy for older patients. However, the change of FS during chemotherapy is rarely studied as GA is mostly performed once instead of sequentially.